Examining school leadership effects on student achievement: the role of contextual challenges and constraints. Issue 1 (2nd January 2018) - Tan, Cheng Yong
Abstract: The present study examined indirect effects of principal leadership on the mathematics achievement of 254, 475 15-year-old students from 10, 313 schools in 32 OECD economies. Results showed that the students could be divided into three categories ( Disadvantaged, Average, and Privileged ) differing in levels of student SES and prior achievement, parental academic expectations, and access to school resources. Results also showed that principal leadership effects accounted for a greater proportion of between-school achievement variance for Disadvantaged vis-à-vis Privileged or Average students. In particular, instructional leadership had the largest positive effect on Disadvantaged vis-à-vis other students' achievement via the mediating variables of teacher autonomy and morale. Distributed leadership negatively affected the achievement of Disadvantaged but not other students. The negative effects of principal goal-setting were the largest while those of principal problem-solving were the smallest for Disadvantaged students. The study contributes to the literature by examining contextual influences on the leadership–achievement relationship.